The predictive potential of surrogate indicators of insulin resistance for type 2 diabetic kidney disease - Tian, Qiuhui; Liu, Yu; Cao, Qiumei; Zhang, Meixu; Zhu, Fengying; He, Yukai; Zhu, Xiaoling (Frontiers in Endocrinology, 2026)
BackgroundApproximately 40% of patients with diabetes develop diabetic kidney disease (DKD), necessitating renal replacement therapy such as dialysis or transplantation. Furthermore, DKD significantly elevates the risk of cardiovascular events and all-cause mortality, while imposing a substantial economic burden on healthcare systems. This study investigates the association between surrogate markers of insulin resistance (IR)—the triglyceride-glucose (TyG) index, TyG-body mass index (TyG-BMI), and the triglyceride-to-high-density lipoprotein cholesterol ratio (TG/HDL-C)—and DKD in individuals with type 2 diabetes mellitus (T2DM), evaluating their predictive utility for DKD progression.MethodsWe enrolled 311 patients diagnosed with T2DM between January 2024 and April 2025. Baseline clinical characteristics and variations in IR markers across proteinuria stages were analyzed. Multivariable logistic regression assessed the association between these markers and DKD, while receiver operating characteristic (ROC) curve analysis evaluated their predictive performance. Restricted cubic spline (RCS) models explored dose-response relationships, supplemented by subgroup and interaction analyses.ResultsHigher quartiles of TyG, TyG-BMI, and TG/HDL-C were significantly associated with increased DKD risk (trend P < 0.001). ROC analysis revealed moderate-to-strong predictive accuracy for all three markers (AUC > 0.7). RCS modeling indicated a linear relationship between TyG and DKD risk (nonlinearity P = 0.378), whereas TyG-BMI and TG/HDL-C exhibited nonlinear associations (nonlinearity P < 0.05). Subgroup analysis identified a significant gender interaction for TG/HDL-C, with a stronger association in males (interaction P < 0.05). Age did not significantly modify these relationships. The biomarkers’ association with DKD was more pronounced in patients with HbA1c ≥ 7%, while the TyG-BMI–DKD link was weaker in those with HbA1c < 7%. Stratified analysis by BMI showed a significant interaction (interaction P < 0.05).ConclusionTyG, TyG-BMI, and TG/HDL-C are positively correlated with DKD risk in T2DM patients and demonstrate substantial predictive value, supporting their potential as accessible, cost-effective indicators for DKD risk assessment.